Pathogenic variation in, sources of, and breeding for resistance to Phaeoisariopsis griseola causing angular leaf spot in common bean - Pastor Corrales, Marcial A.; Jara, Carlos E.; Singh, Shree P. (Springer, 1998)
If we are to breed common bean (Phaseolus vulgaris L.) for durable resistance to diseases, we must understand pathogenic variation and find sources of resistance. Our first objective was to determine the patterns of pathogenic variation found among isolates of Phaeoisariopsis griseola (PG), the fungus that causes angular leaf spot (ALS) in common bean. We characterized 433 PG isolates from 11 Latin American and 10 African countries, using differential cultivars, isozymes, and/or random amplified polymorphic DNA (RAPD) markers. We also systematically screened, for ALS resistance, common bean accessions from the world collection held at CIAT, and assessed the progress so far made in breeding for resistance to ALS. Despite their great diversity within and between countries on both continents, the PG isolates were classified into two major groups: Andean, and Middle American. Although each group had internal differences for virulence, and biochemical and molecular characteristics, the Andean PG isolates were more virulent on common beans of Andean origin, than on those of Middle American origin, thus, suggesting a host-pathogen co-evolution. The Middle American PG isolates, although more virulent on common beans from Middle America, also attacked Andean beans, thus, exhibiting a much broader virulence spectrum. To find sources of resistance, we tested 22,832 common bean accessions against naturally occurring PG isolates in the field at CIAT's Experiment Station, Quilichao, Colombia, between 1985 and 1992. The resulting 123 intermediate (scores of 4 to 6) and resistant (scores of 1 to 3) accessions were then tested in the greenhouse against selected 14 PG isolates of diverse origins. Nineteen accessions were intermediate or resistant to at least 13 of 14 PG isolates. Similarly, of 13,219 bred lines tested in the field between 1978 and 1996, 89 were intermediate or resistant. Of these, 33 bred lines proved intermediate or resistant to at least eight of nine PG isolates to which they were challenged in the greenhouse. We suggest that, to breed for durable resistance to ALS, common bean populations should be developed from crosses between Andean and Middle American gene pools. The populations should then be systematically evaluated and selected against the broadest range of the most virulent PG isolates of diverse evolutionary origins.